Pengaruh Penggunaan Pupuk Organik dan Benih Unggul Terhadap Hasil Produksi Usahatani Terong Ungu di Desa Duriaasi Kabupaten Konawe - Niar Fitriani; La Karimuna; Kalis Amartani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The aim of this research is to analyze the effect of using superior seed organic fertilizer on the production of purple eggplant farming in Duriaasi Village, Wongeduku District, Konawe Regency. This research will be in Duriaasi Village, Wongeduku District, Konawe Regency. Determining the location of this research was carried out purposively, namely a method of deliberately determining the research area. Sample determination was carried out by census. Where in Duriaasi Village there are 35 purple eggplant farmers. The analysis uses a multiple non-linear regression formula with the equation transformed in linear form or in the form of the Cobb-Douglas function. Based on the results of research on respondent farmers who manage purple eggplant farming in Duriaasi Village, it can be concluded that the compost fertilizer production factor has a significant influence on purple eggplant production. Meanwhile, manure production factors, superior seeds Bungo F1, superior seeds Panah Merah Yuvita F1 did not have a significant effect on purple eggplant production